Focus on Autoimmune Myocarditis in Graves' Disease: A Case-Based Review - Wu, Lujin; Wang, Wei; Leng, Qianru; Tang, Nana; Zhou, Ning; Wang, Yan; Wang, Dao Wen (Frontiers in Cardiovascular Medicine, 2021)
The manifestations of hyperthyroidism related myocardial damage are multitudinous, including arrhythmia, dilated cardiomyopathy, valvular diseases and even cardiogenic shock. Acute myocarditis induced by thyrotoxicosis had been reported in few studies. However, the attention of its prevalence and underlying mechanisms are sorely lacking. Its long-term harm is often ignored and may eventually develop into dilated cardiomyopathy and heart failure. We report a case of Graves' disease (GD) with progressive elevation of hypersensitive cardiac troponin-I (hs-cTnI) at several days after discontinuation of her anti-thyroid drugs (ATDs). Cardiac magnetic resonance imaging (CMRI) showed inflammatory edema of some cardiomyocytes (stranded enhanced signals under T2 mapping), myocardial necrosis (scattered enhanced signals under T1 LGE) in the medial and inferior epicardial wall, with decreased left ventricular systolic function (LVEF = 48%), which implied a possibility of acute myocarditis induced by thyrotoxicosis. The patient was then given a transient glucocorticoid (GC) treatment and achieved good curative effect. Inspired by this case, we aim to systematically elaborate the pathogenesis, diagnosis and treatment of hyperthyroidism-induced autoimmune myocarditis. . Additionally, we emphasize the importance of CMRI and GC therapy in the diagnosis and treatment of hyperthyroidism related myocarditis.